Super Bowl Sunday: Risky Business for At-Risk (Male) Drinkers?. (24th August 2014) - Dearing, Ronda L.; Twaragowski, Cheryl L.; Smith, Philip H.; Homish, Gregory G.; Connors, Gerard J.; Walitzer, Kimberly S.
<x xml:space="preserve">Abstract</x> Background: Major sporting events and other festive occasions are typically associated with alcohol consumption; however, little is known about risky drinking during events such as the "Super Bowl." Objectives: We sought to determine whether drinking on Super Bowl Sunday differed from Saturdays (the heaviest drinking day of the week) surrounding the date of the Super Bowl among at-risk drinkers. Methods: Heavy drinking participants (N = 208) were recruited via advertisements for a 2-year prospective study of drinking behaviors. From this larger sample, 196 were selected for whom the date of the Super Bowl was included in their daily alcohol consumption reports (including reports of abstinence on those days) for 2006, 2007, and/or 2008. Participants' average age was 36.4 (SD = 12.9); 49.5% were women. Participants at the point of recruitment were not seeking treatment and had not been in alcohol treatment in the past year. Results: Analyses using multilevel modeling comparing Super Bowl Sunday to Saturdays indicated that men drank more alcohol on Super Bowl Sunday across all 3 years, whereas women's drinking was higher in only one of the 3 years. Conclusions/Importance: These findings suggest that heavy drinking during the Super Bowl (and in association with other sporting events), particularly among men, warrants additional attention due to the potential for deleterious public health consequences.